Water in the Parables of Worldly Life in the Qur'an: A Semantic and Scientific Study - Rochmad, R; Nasution, Alhafidh; Anggara, Deki Ridho Adi; Rifaannudin, Mahmud; Almaarif, Mohammad Abdul Hafidz Annafi (QiST: Journal of Quran and Tafseer Studies, 2025)
This study aims to analyze the parables of worldly life that are likened to water in the Qur'an. using semantic and scientific approaches. This parable, found in Surah Yunus (10:24), Al-Kahf (18:45), and Al-Hadid (57:20), conveys an essential message about the transient nature of life to prevent humans from being deceived by temporary pleasures. This research is a library study employing a descriptive-analytical method, with data collected from primary and secondary sources. The semantic approach is used to uncover the meaning of worldly life in the Qur'an, while the scientific approach examines the characteristics of water mentioned in the related verses. The findings reveal that the Qur'an highlights the similarities between worldly life and water, both being impermanent, rapidly changing, and significantly impactful when utilized properly. These similarities emphasize the temporary and dynamic nature of worldly life, urging humans to reflect upon its reality and avoid indulgence in arrogance and excessive enjoyment. Despite its findings, this study has limitations, and further research is encouraged to explore the parables of worldly life in the Qur'an with a more comprehensive semantic and scientific approach.